2019 IEEE International Symposium on Information Theory (ISIT) 2019
DOI: 10.1109/isit.2019.8849295
|View full text |Cite
|
Sign up to set email alerts
|

From Classical to Semi-Quantum Secure Communication

Abstract: In this work we introduce a novel QKD protocol capable of smoothly transitioning, via user-tuneable parameter, from classical to semi-quantum in order to help understand the effect of quantum communication resources on secure key distribution. We perform an information theoretic security analysis of this protocol to determine what level of "quantumness" is sufficient to achieve security, and we discover some rather interesting properties of this protocol along the way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In [24], it was shown that A need only measure in the X basis and send three states. In [25], it was shown that A needed only to prepare two states, a |0 and a state |a where | 0|a | ∈ (0, 1) while only measuring using a three outcome POVM. This last paper provided an SQKD protocol that could smoothly transition from classical communication to (semi) quantum communication and proposed a method of measuring the affects this transition has on secure communication rates.…”
Section: Usersmentioning
confidence: 99%
See 4 more Smart Citations
“…In [24], it was shown that A need only measure in the X basis and send three states. In [25], it was shown that A needed only to prepare two states, a |0 and a state |a where | 0|a | ∈ (0, 1) while only measuring using a three outcome POVM. This last paper provided an SQKD protocol that could smoothly transition from classical communication to (semi) quantum communication and proposed a method of measuring the affects this transition has on secure communication rates.…”
Section: Usersmentioning
confidence: 99%
“…Proof Comments Tolerance Reference BKM07 [7] 11% [60] Single State by Zou et al, [15] 9.65% [71] Reflection-Based [16] 5.36% [64] Semi-Quantum B92 [20] 3.46% [20] Single-A-Measurement [24] 11% [24] MM Required Classical-to-Quantum [25] < 1% [25] MM Required; Noise tolerance depends on distance from classical. High-Noise-SQKD M2 [31] 16.4% [31] High-Noise-SQKD M3 [31] 26% [31] High-Dimensional SQKD [39] 30% [39] Noise tolerance increases to 30% as dimension approaches infinity Table 2: Showing state of the art best noise tolerances for those SQKD protocols which have this analysis performed.…”
Section: Noisementioning
confidence: 99%
See 3 more Smart Citations